MEMORY AND HIPPOCAMPAL ARCHITECTURE FOLLOWING SHORT-TERM MIDAZOLAM IN WESTERN DIET-TREATED RATS - Rosenberger, Dorothea S. (Neurosci Lett, 2016)
The impact of short-term benzodiazepine exposure on cognition in middle-aged or older patients is a highly debated topic among anesthesiologists, critical care physicians and public media. “Western diet” (WD) consumption is linked to impaired cognition as well. The combination of benzodiazepines with substantial exposure to WD might set the stage for increased hippocampal vulnerability for benzodiazepines leading to exaggerated cognitive impairment in the postoperative period. In this study, Fischer 344 rats were fed either WD or standard rodent diet from 5 to 10.5 months of age. Rats were exposed to midazolam or placebo two days prior to an MRI scan using Diffusional Kurtosis Imaging (DKI) to assess brain microstructural integrity, followed by behavioral testing using a water radial arm maze. Hippocampal tissue was collected to assess alterations in protein biochemistry in brain regions associated with learning and memory. Our results showed that rats exposed to the combination of midazolam and WD had significantly delayed time of learning and exhibited spatial memory impairment. Further, we observed an overall increase of kurtosis metrics in the hippocampus and increased expression of the mitochondrial protein VDAC2 in midazolam-treated rats. Our data suggest that both the short-acting benzodiazepine midazolam and WD contribute to negatively affect the brain in middle-aged rats. This study is the first application of DKI on the effects of midazolam and WD exposure, and the findings demonstrate that diffusion metrics are sensitive indicators of changes in the complexity of neurite architecture.